Carut Marut Politik, Tantangan Pengembangan Teologi Politik Substantivistik - Abd A'la (Unisia, 2005)
The political changes that have been experiencing by the Indonesian since the era of reformation show a face of ambivalence. On one hand, the freedom comes with the exciting expectation from the peopie of this country. On the other hand, the phenom enon has been showing that the political authorization is going on the process accompanied by ethic and moral degradation. This issue has brought Indonesia in a difficult situation and far from justice, peace, and weifare. However, a religious country has been claim by Indonesian as a character of this nation. This paper discusses political Issues in Indonesia focusing on the current Indonesian politic, the root of the country's problem; the religion at the centre of the reformation, and the political value of the religion with the significant of the politicai theology.